Epigenetic Regulation of Cellular Senescence and Aging - Sidler, Corinne; Kovalchuk, Olga; Kovalchuk, Igor (Frontiers in Genetics, 2017)
Aging is not only associated with the functional decline of diverse organs, but also with an increased risk for several diseases. Therefore, a high interest exists in understanding the molecular mechanisms that stimulate aging at all levels, from cells and tissues to organs and organisms, in order to develop ways to promote healthy aging. While many molecular and biochemical mechanisms are already understood in some detail, the role of changes in epigenetic regulation has only begun to be considered in recent years. The age-dependent global reduction in heterochromatin, along with site-specific changes in DNA methylation and histone modification patterns, have been observed in several aging model systems. However, understanding of the precise role of such changes requires further research. In this article, we will review the literature on the role of epigenetic regulation in aging and indicate future research directions that will help elucidate the mechanistic details of it.